2021
DOI: 10.1177/20322844211028308
|View full text |Cite
|
Sign up to set email alerts
|

Ireland: Curtailment of the right to silence through statutory adverse inferences

Abstract: In Ireland, the right to silence has been significantly impacted by the legislative introduction of adverse inference provisions. In specified circumstances, with varying threshold requirements, a suspect’s failure to answer questions or provide information during Garda (police) questioning can form the basis of an inference against them at trial. Ireland has not opted in to either Directive 2016/343/EU on the strengthening of certain aspects of the presumption of innocence or Directive 2013/48/EU on the right… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Most notably, in the context of this article, Ireland has not opted in to Directive 2016/343/EU on the strengthening of certain aspects of the presumption of innocence, or indeed to Directive 2013/48/EU on the right of access to a lawyer in criminal proceedings. The Irish Department of Justice appears to believe that the existence of Ireland's legislative inferences makes it impossible for the state to fulfil the terms of Directive 2012/13/EU (Daly, 2021), but this is not without question. Commentators (Pivaty et al 2021) have observed that the final wording of Directive 2012/13/EU allows for a number of possible interpretations such that its asserted prohibition on the use of adverse inference might not be as definitive as originally foreseen when the Directive was first considered.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most notably, in the context of this article, Ireland has not opted in to Directive 2016/343/EU on the strengthening of certain aspects of the presumption of innocence, or indeed to Directive 2013/48/EU on the right of access to a lawyer in criminal proceedings. The Irish Department of Justice appears to believe that the existence of Ireland's legislative inferences makes it impossible for the state to fulfil the terms of Directive 2012/13/EU (Daly, 2021), but this is not without question. Commentators (Pivaty et al 2021) have observed that the final wording of Directive 2012/13/EU allows for a number of possible interpretations such that its asserted prohibition on the use of adverse inference might not be as definitive as originally foreseen when the Directive was first considered.…”
Section: Discussionmentioning
confidence: 99%
“…Commentators (Pivaty et al 2021) have observed that the final wording of Directive 2012/13/EU allows for a number of possible interpretations such that its asserted prohibition on the use of adverse inference might not be as definitive as originally foreseen when the Directive was first considered. In discussing the need to continue those provisions in operation the Irish Minister for Justice and Equality stated in 2019 that such provisions are ‘a key tool in the investigation and prosecution of serious crime’ 41 (Daly, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation